A photoredox catalysed Heck reaction via hole transfer from a Ru(ii)-bis(terpyridine) complex to graphene oxide. Issue 70 (25th November 2020) - Rosenthal, Marta; Lindner, Jörg K. N.; Gerstmann, Uwe; Meier, Armin; Schmidt, W. Gero; Wilhelm, René
Abstract : A hole transfer from an excited Ru unit towards graphene oxide significantly improved the photocatalytic activity of the complexes. Abstract : The attachment of homoleptic Ru bis-terpy complexes on graphene oxide significantly improved the photocatalytic activity of the complexes. These straightforward complexes were applied as photocatalysts in a Heck reaction. Due to covalent functionalization on graphene oxide, which functions as an electron reservoir, excellent yields were obtained. DFT investigations of the charge redistribution revealed efficient hole transfer from the excited Ru unit towards the graphene oxide.